The Role of Work Alienation in the Relationship Between Perceived Organizational Injustice and Counterproductive Work Behaviors - Amzulescu, Gabriel; Butucescu, Andreea (Psihologia Resurselor Umane, 2021)
Previous studies supported the relationship between perceived organizational injustice and counterproductive behaviors at work, and in the current research the emphasis is on the explanatory mechanism of alienation. This study aims to investigate whether work alienation could be a potential mediator in the relationship between the two constructs. In an attempt to research an explanatory mechanism that is less addressed in the literature, a non-experimental cross-sectional study was conducted, based on a sample of 145 participants from different industries. The statistical analysis’ results indicated that perceived organizational injustice is a significant predictor of counterproductive behavior. Furthermore, workplace alienation has completely mediated the relationship between perceived organizational injustice and employees’ counterproductive behaviors. These findings reiterate the role and importance of employees' perceptions of organizational justice in the emergence and possible reduction of counterproductive behaviors that are detrimental to both the organization and individuals. The data obtained also supported a possible explanatory mechanism of their relationship.